CUSTOMER-DRIVEN EXCELLENCE STRATEGY: LEVERAGING SERVICE QUALITY, BRAND CREDIBILITY, AND PERCEIVED VALUE IN THE UMRAH TRAVEL INDUSTRY IN DEPOK CITY - Wulandari, Aghnia; Efendi, Suryono; Hasanudin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the implementation of customer-driven excellence strategy in the Umrah travel industry in Depok City by investigating the relationships between service quality, brand credibility, perceived value, and customer-driven excellence outcomes. Using a quantitative research approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 105 customers who have utilized Umrah travel services within the past two years. The measurement model demonstrated excellent reliability and validity, with all constructs meeting stringent psychometric criteria for convergent and discriminant validity. The structural model reveals that all three hypotheses are strongly supported, with brand credibility emerging as the most influential factor (β = 0.398, p < 0.001), followed by perceived value (β = 0.356, p < 0.001) and service quality (β = 0.285, p < 0.001). The integrated model explains 74.2% of variance in customer-driven excellence, demonstrating strong explanatory power and large predictive relevance (Q² = 0.486). These findings provide empirical evidence that successful customer-driven excellence strategy requires integrated approaches prioritizing brand credibility development while simultaneously enhancing perceived value and service quality. The study offers valuable insights for Umrah travel operators seeking to optimize competitive advantage through comprehensive customer excellence strategies that address both functional and emotional dimensions of religious tourism services.